(untitled) (Stavební obzor - Civil Engineering Journal, 2022)
The paper presents partial results of the expert cooperation between geologists and historians in the Bohemian Switzerland (Elbe Sandstones) area focused on mapping and documentation of old quarries and mining pits. More than three thousand abandoned quarries for building stone were newly mapped and registered within the study area. Attention was given not only to the preserved relics after mining and their historical context: methods of stone extraction were also described, and the current state of quarries and mining areas was documented. Many of them represent unstable quarry faces prone to rockfall. Catastrophic events have already occurred in some quarries, and some localities had to be technically secured by stabilizing works recently. One of the aims was therefore to create an inventory map of risk related to old quarries and the assessment of the present-day degree of instability. Fresh rockfalls from 2021/2022 were also registered. Three-dimensional models of selected quarry faces were created using modern technology including calculation of cubic capacity of excavated material and collapsed masses. The complete results are included in the map geodatabase, which is under construction.